Drip irrigation biofouling with treated wastewater: bacterial selection revealed by high-throughput sequencing. Issue 2 (7th February 2019) - Lequette, Kévin; Ait-Mouheb, Nassim; Wéry, Nathalie
Abstract: Clogging of drippers due to the development of biofilms weakens the advantages and impedes the implementation of drip irrigation technology. The objective of this study was to characterise the bacterial community of biofilms that develop in a drip irrigation system supplied with treated wastewater. High-throughput sequencing of 16S rRNA gene amplicons indicated that the bacterial community composition differed between drippers and pipes, mainly due to changes in the abundance of the genus Aquabacterium . Cyanobacteria were found to be involved in the biological fouling of drippers. Moreover, bacterial genera including opportunistic pathogenic bacteria such as Legionella and Pseudomonas were more abundant in dripper and pipe biofilms than in the incoming water. Some genera such as Pseudomonas were mostly recovered from drippers, while others (ie Bacillus, Brevundimonas ) mainly occurred in pipes. Variations in the hydraulic conditions and properties of the materials likely explain the shift in bacterial communities observed between pipes and drippers.